Efektivitas Aromatherapy Lavender Dalam Mengurangi Gejala Mual Muntah Pada Ibu Hamil - Norsela, Norsela; Alfitri, Rosyidah (Madu : Jurnal Kesehatan, 2024)
Pregnancy is a process of development of the results of the development of the results of the seeding process until birth. During the pregnancy process there are many uncomfortable feelings, one of which is nausea and vomiting. Nausea and vomiting will be dangerous if not treated properly, one of the consequences is impaired fetal development, so it is necessary to take preventive measures and safe therapy for pregnant women and fetuses. Quasy-Experimental conducted at PMB Norita Dahlia to pregnant women in the first trimester who complained of nausea and vomiting, in May and June 2024. A total of 20 research samples were obtained that met the inclusion criteria. The samples were asked to fill out the initial PUQE Questionnaire as a pretest result, and were given Lavender Aromatherapy, and were asked to return in 3 days and fill out the PUQE questionnaire again. Data were analyzed using the Wilcoxon Test Lavender Aromatherapy effective in reducing the severity of nausea and vomiting based on the PUQE questionnaire. (Z = -3.986, S <0.00). Lavender Aromatherapy is effective in reducing the rate of nausea and vomiting in pregnant women in the first trimester.